“`Las relaciones sexuales y las habilidades sociales de los estudiantes Carrera de Psicología Educativa, de la Universidad Nacional de Chimborazo, abril – agosto 2019” - Edison Alejandro, Chuqui Samaniego (2020)
The following project was carried out to establish the relationship between social skills and sexual relations in students of the educational psychology career of the academic period April-August 2019, knowing that it is moderately approved among professionals dealing with conflicts that occur in couple and that have an impact on the social sphere since the fact of not having sexual relations makes them emotionally unhappy, they have feelings of depression, personal insecurity, less ability to concentrate and especially low self-esteem; in addition there are studies that have shown that all Aspects related to sexuality have an impact on the construction of the I, emphasizing social behavior. Regarding the methodology, it was taken as a mixed approach, its design was non-experimental, as well as a cross-sectional field research, basic and level of correlational research. The universe of study was the students of the seventh semester, for which the sample was of an intentional non-probabilistic type and consists of 59 students that are subdivided into 46 women and 13 men. The instruments used in the research for the independent variable was the technique of A survey consisting of 12 questions and the social skills scale known as Elena Gismero's psychometric test for the dependent variable. Once the research was carried out and the reagents were applied, it was verified that the fact of not having a sexual relationship affects not only the couple's life but also fully affects social behavior.